2017
DOI: 10.1016/j.neuropharm.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for the novel estrogen-sensing receptor GPER1 in the CNS

Abstract: Keywords: G protein coupled estrogen receptor, hippocampal synaptic function; receptor trafficking; learning and memory; neuroprotection; synaptic plasticity. Estrogens play a key role in regulating reproductive and neuroendocrine function by activating classical nuclear steroid receptors that act as ligand gated transcription factors.However evidence is growing that estrogens also promote rapid non-genomic responses via activation of membrane-associated estrogen receptors. The G protein-coupled estrogen recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 130 publications
0
47
0
Order By: Relevance
“…It is well documented that the central effects of E 2 are mediated by the classical oestrogen receptors (ERs), ERα and ERβ, which function as transcription factors that are able to regulate the activity of different genes, as well as by the membrane‐bound G protein‐coupled oestrogen receptor GPER1 (also called GPR30), which mediates rapid non‐genomic effects . Increasing evidence supports a major role for GPER1 with respect to mediating the neuroprotective effects of oestrogens on the main cognitively relevant brain structures . All types of oestrogen receptors have been localised in multiple brain areas and are expressed in varying densities in both sexes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that the central effects of E 2 are mediated by the classical oestrogen receptors (ERs), ERα and ERβ, which function as transcription factors that are able to regulate the activity of different genes, as well as by the membrane‐bound G protein‐coupled oestrogen receptor GPER1 (also called GPR30), which mediates rapid non‐genomic effects . Increasing evidence supports a major role for GPER1 with respect to mediating the neuroprotective effects of oestrogens on the main cognitively relevant brain structures . All types of oestrogen receptors have been localised in multiple brain areas and are expressed in varying densities in both sexes .…”
Section: Introductionmentioning
confidence: 99%
“…24 Increasing evidence supports a major role for GPER1 with respect to mediating the neuroprotective effects of oestrogens on the main cognitively relevant brain structures. 25 All types of oestrogen receptors have been localised in multiple brain areas and are expressed in varying densities in both sexes. 26,27 However, it has been suggested that GPER1 activation may be particularly involved in mediating the positive effects of E 2 on cognitive performance at the level of cholinergic afferents innervating the hippocampus and cortex, 28,29 thereby directly acting on hippocampal synaptic function.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen is the primary female sex hormone with a crucial role in the regulation of reproductive and neuroendocrine function. Different studies reported that estrogen also modulates synaptic plasticity in the hippocampus, regulates the formation of amyloid-β peptide, inactivates the expression of proapoptotic factors, and demonstrates antioxidant activity [8].…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear ER are either ERα or ERβ, which are responsible for the estrogen genomic action through regulation of various transcriptional gene expression mechanisms. The brain contains both types of nuclear ER, which are abundant in the hippocampus, pyramidal cells and glial tissue [42]. The membrane estrogen receptors (mERs) are G protein-coupled and ligand-gated ion channels, including GPER1 (previously known as GPR30), ER-X and Gq-mER, which are responsible for the rapid nongenomic actions of estrogen that is initiated within minutes after estrogen administration (estrogen neurotransmitter actions) due to recruitment and activation of kinase-dependent signaling pathways.…”
Section: Estrogen Actions In Normal Cognitionmentioning
confidence: 99%